Reporting sexual violence on mental health wards. Issue 2 (9th April 2018) - Foley, Marian; Cummins, Ian
Abstract : Purpose: The purpose of this paper is to report the findings of a scoping study that explored the extent of recorded sexual violence perpetrated on inpatients on mental health (MH) units. Design/methodology/approach: A Freedom of Information Act (FOI) request was sent to 45 police forces. The FOI asked for the number of recorded offences of rape and sexual assault by penetration for the five years 2010-2015. Following the responses from the police, a similar FOI request was sent to MH trusts. Findings: There were significant variations in the way that both police forces and MH trusts approached the recording of this information. Research limitations/implications: The research highlights variation and inadequacy of current recording practices in relation to sexual offences committed against inpatients on MH units. Practical implications: There needs to be more consistent systems of recording of allegations of sexual assault and responses to them by agencies. In the trust recording of these incidents, it is recommended that a specific category of sexual violence is created. On a national level, the Office for National Statistics should produce a national data set that records the number of rapes that are committed in MH inpatient units. Originality/value: This paper highlights the "gap" of information in relation to recorded rape and may indicate that complainants with a history of mental illness are less likely to have their allegation recorded as a crime.